Enriched environment promotes post-stroke angiogenesis through astrocytic interleukin-17A - Chen, Xiuping; Liu, Lingling; Zhong, Yingjun; Liu, Yang (Frontiers in Behavioral Neuroscience, 2023)
Objective Our previous studies have revealed that the protective effect of an enriched environment (EE) may be linked with astrocyte proliferation and angiogenesis. However, the relationship between astrocytes and angiogenesis under EE conditions still requires further study. The current research examined the neuroprotective effects of EE on angiogenesis in an astrocytic interleukin-17A (IL-17A)-dependent manner following cerebral ischemia/reperfusion (I/R) injury. Methods A rat model of ischemic stroke based on middle cerebral artery occlusion (MCAO) for 120 min followed by reperfusion was established, after which rats were housed in either EE or standard conditions. A set of behavior tests were conducted, including the modified neurological severity scores (mNSS) and the rotarod test. The infarct volume was evaluated by means of 2,3,5-Triphenyl tetrazolium chloride (TTC) staining. To evaluate the levels of angiogenesis, the protein levels of CD34 were examined by means of immunofluorescence and western blotting, while the protein and mRNA levels of IL-17A, vascular endothelial growth factor (VEGF), and the angiogenesis-associated factors interleukin-6 (IL-6), JAK2, and STAT3 were detected by western blotting and real-time quantitative PCR (RT-qPCR). Results We found that EE promoted functional recovery, reduced infarct volume, and enhanced angiogenesis compared to rats in standard conditions. IL-17A expression in astrocytes was also increased in EE rats. EE treatment increased the levels of microvascular density (MVD) and promoted the expression of CD34, VEGF, IL-6, JAK2, and STAT3 in the penumbra, while the intracerebroventricular injection of the IL-17A-neutralizing antibody in EE rats attenuated EE-mediated functional recovery and angiogenesis. Conclusion Our findings revealed a possible neuroprotective mechanism of astrocytic IL-17A in EE-mediated angiogenesis and functional recovery after I/R injury, which might provide the theoretical basis for EE in clinical practise for stroke patients and open up new ideas for the research on the neural repair mechanism mediated by IL-17A in the recovery phase of stroke.